High Response Rate and Prolonged Survival of Unresectable Biliary Tract Cancer Treated With a New Combination Therapy Consisting of Intraarterial Chemotherapy Plus Radiotherapy - Goto, Takuma; Saito, Hiroya; Sasajima, Junpei; Kawamoto, Toru; Fujinaga, Akihiro; Utsumi, Tatsuya; Yanagawa, Nubuyuki; Hiramatsu, Kazuhide; Takamura, Akio; Sato, Hiroki; Fujibayashi, Shugo; Fujiya, Mikihiro (Frontiers in Oncology, 2020)
Synopsis: A new combination therapy consisting of intraarterial chemotherapy plus radiotherapy was demonstrated to have the potential to improve the response rate and survival time in patients with unresectable biliary tract cancer. Purpose: We retrospectively investigated the effectiveness and safety of a new combination therapy consisting of intraarterial chemotherapy plus radiation therapy (AI+RT), which may have the potential to improve unresectable biliary tract cancer (BTC). Methods: We retrospectively reviewed 52 BTC cases treated with AI+RT and analyzed the anti-tumor effect, survival time and adverse events. The AI+RT regimen consisted of one-shot intraarterial chemotherapy (AI) at the first angiography session, almost 6 months of reservoir AI (5-FU and cisplatin, q/week) and external radiation with a maximum dose of 50.6 Gy. Results: The response rate and disease control rate were high, at 40.4% and 96.2%, respectively, and the median overall and progression-free survival time were 463 and 431 days; thus, long-term survival was achieved. A univariate analysis identified 11 prognostic factors, and a performance status of 2 (hazard ratio [HR]: 4.45, p=0.02), jaundice (HR: 3.84, p<0.01), peritoneal dissemination (HR: 18.2, p<0.01), number of AI (HR: 0.36, p=0.01) and response to AI+RT (HR: 0.22, p<0.01) were extracted as significant prognostic factors in a multivariate analysis. The following: grade ≥3 adverse events occurred: leucopenia (11.5%), neutropenia (1.9%), anemia (15.4%), thrombocytopenia (11.5%), anorexia (3.8%), gastroduodenal ulcer (25.0%) and cholangitis (23.1%). There were no cases of treatment-related death. Conclusions: AI+RT was shown to contribute to a high response rate and prolonged survival in patients with unresectable BTC. A sufficient number of AI and the response to this therapy were thought to be significant prognostic factors in patients receiving AI+RT. Advances in multidisciplinary therapies, such as AI+RT, which was described in the present study, are also considered to be important for the future.